Can critical research influence policy? A response to Max Travers - Bridges, Judith S. (The British journal of criminology, 1997)
Questions whether criminal justice research influence policy, highlighting arguments by authors David Smith and Max Travers. Reference to the books `The Case for the Prosecution,' and `Standing Accused'; Description of Travers' views of research